1992
DOI: 10.1002/path.1711660407
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of regenerating cells after submassive liver necrosis using PCNA staining

Abstract: Little data exist on the proliferative state of liver cells and its relationship with various morphological findings in acute liver failure (ALF) in man. In this study we used the monoclonal antibody NCL-PCNA (clone PC-10) against the proliferating cell nuclear antigen (PCNA) to detect cycling cells in paraffin sections of 3 normal livers, 14 post-mortem needle-specimens of submassive hepatic necrosis (SHN) due to paracetamol overdosage (POD), and 10 hepatectomy specimens obtained at transplantation in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…This confirms previous observations in humans. [7][8][9][10][11] Ductular reaction tends to be mild in degree and fades over a period of approximately 1 to 2 weeks. Hepatocytes derived from hepatic progenitors do not appear involved in the regenerative process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms previous observations in humans. [7][8][9][10][11] Ductular reaction tends to be mild in degree and fades over a period of approximately 1 to 2 weeks. Hepatocytes derived from hepatic progenitors do not appear involved in the regenerative process.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although in acetaminophen-induced injury proliferation of mature hepatocytes seems to be the main regenerative mechanism, this cannot be accurately assessed in seronegative liver failure because of the patchy nature of the initial damage leading to considerable sampling variation in subsequent core needle specimens. Assessment of cell proliferation by proliferating cell nuclear antigen immunostaining of explanted livers with map-like injury 7 has shown that in the nodular areas of parenchyma, hepatocellular nuclear staining is heterogeneous and maximal in areas adjacent to confluent cell loss or to portal tracts. This ranges from 10% to 50%, whereas in areas of multiacinar cell dropout, 10% to 35% of ductular epithelial cells are cycling; this suggests that expansion of a stem cell or progenitor cell compartment may be the regenerative response in areas of complete hepatocyte loss.…”
Section: Discussionmentioning
confidence: 99%
“…The marked increase in PCNA-positive hepatocytes in early hepatic regeneration indicates that they are activated to repair intracellular damage as well as prepare to replicate because PCNA is involved in DNA repair and replication (13,(19)(20)(21). Sinusoidal PCNA-positive cells are considered to be activated Kupffer cells or macrophages on the basis of their location and nuclear shape as indicated previously (19).…”
Section: Discussionmentioning
confidence: 92%
“…However, it was impossible in human cases ethically as well as practically due to the limitation of obtaining the samples. Thus broad spectrum of histopathologic changes during hepatic regeneration have been rarely documented in human livers (4,11,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…7,15,[33][34][35] This correlates with the low PCNA-LI observed in normal livers. The current study shows a dramatic increase of hepatocyte proliferative activity in most cases of cirrhosis.…”
Section: Discussionmentioning
confidence: 93%